THU0631 Refractory and severe uveitic cystoid macular oedema improves with tocilizumab in different immune-mediated inflammatory diseases. (12th June 2018) - Vegas-Revenga, N.; Calvo-Río, V.; Mesquida, M.; Adán, A.; Hernandez, M.; Beltrán, E.; Valls Pascual, E.; Díaz-Valle, D.; Díaz-Soriano, G.; Hernandez-Grafella, M.; Martínez-Costa, L.; Calvo, I.; et al.
Abstract : Background: Cystoid macular oedema (CME) represents the leading cause of blindness in uveitis of different immune-mediated inflammatory diseases (IMIDs). Objectives: Our aim was to evaluate the efficacy of Tocilizumab (TCZ) in different IMIDs with refractory CME. Methods: Multicentre study of 24 patients with CME due to uveitis of different IMIDs refractory to traditional treatment with systemic corticosteroids and at least one conventional immunosuppressive drug including in most cases biological therapy (n=21). CME was defined by (OCT >300 µm). We studied CME with TCZ in 4 different IMID; juvenile idiopathic arthritis (JiA), Behçet's disease (BD), Birdshot retinochoroidopathy (BR) and idiopathic. The main outcome was the improvement of macular thickness. Other variables assessed were inflammation of the anterior chamber and vitreous and best corrected visual acuity (BCVA) Results: We studied 16 ♀/8 ♂, mean age 35.2±19.3 years. The associated diseases were: JiA (n=9), BD, 7 BR 4 and idiopathic. 4 The ocular patterns were: panuveitis, 9 anterior uveitis, 6 posterior uveitis 5 and intermediate uveitis. 4 Most patients had bilateral involvement. 22 The biological therapy used before the administration of TCZ were infliximab, 8 adalimumab, 18 etanercept, 2 golimumab, 2 rituximab, 2 abatacept, 3 anakinra 1 and daclizumab. 1 TCZ administration schedule was 8 mg/kg/4 weeks iv. 23 or every 2 weeks. 1 TCZ was used in monotherapy 12 or combined with conventional immunosuppressive drugs. 12 OCT values improved considerably in 12 months: in JiA from 340.6±134.1 µm to 252.5±30 µm, in BD from 375.1±117 µm to 235±7.1 µm, in BR from 550.7±214.4 µm to 295.5±43.2 µm and in idiopathic from 515±219.6 µm to 208.3±46.7 µm ( figure 1). Inflammation in anterior chamber and vitritis and BCVA also improved in the 4 subtypes. No minor side effects were observed, so no patient had to stop treatment. Conclusions: TCZ seems a rapid effective treatment in severe and refractory uveitic CME, regardless of the underlying IMIDs. References: [1] Calvo-Río V, de la Hera D. et al. Tocilizumab in uveitis refractory to other biologic drugs: a study of 3 cases and a literature review. Clin Exp Rheumatol2014;32(Suppl 84):S54–S57. [2] Calvo-Río V, Santos-Gomez M, et al. Anti-IL6-R Tocilizumab for Severe Juvenile Idiopathic Arthritis-Associated Uveitis Refractory to anti-TNF therapy. A multicenter study of 25 patients. Arthritis Rheumatol 2016;69:668–75. [3] Calvo-Río V, Blanco R, Santos-Gómez M, et al. Efficacy of Anti-IL6-Receptor Tocilizumab in Refractory Cystoid Macular Edema of Birdshot Retinochoroidopathy Report of Two Cases and Literature Review. Ocul Immunol Inflamm2017Oct;25(5):604–609. Disclosure of Interest: None declared